Obraz Krakowa w publikacjach encyklopedycznych i słownikowych (1733-1830) - Norkowska, Aleksandra (Przybylski i inni : o znaczeniu Krakowa i regionu w kulturze oświecenia, 2019)
THE IMAGE OF KRAKOW IN ENCYCLOPAEDIC AND DICTIONARY PUBLICATIONS (1733-1830) The subject of the article is the image of Krakow contained in the compendia of encyclopedic and dictionary character which were published in the time of the enlightenment (1733- 1830). The work discusses the tendencies that can be observed in the perception of the city, the durability and repeatability of the motives, the authors’ attitude towards current events, and the mechanisms and ways of formulating their statements. The focus of research also includes the attribution of key words and indication of the sources from which Polish, German, British and French encyclopedists drew their information.